Etude de quelques équation et d’inclusion Différentielles fractionnaires - Abde Louaheb Zahzouh (My University, 2025)
In general, the existence of solutions for fractional differential equations, inclusion and other mathematical problems is greatly helped by the study of the theory of fixed points, and other methods...ect. In this thesis, by using the fixed point theory for single and multi-valued mapping, we give some results for the following problems with tow points boundary conditions The first case, when ƒ is a single-valued mapping 0+ u (t) = ƒ (t, u (t)) , t ∈ [0, 1], (1) u(0) = u(1) = 0 où 1 < α < 2, cD the standard Caputo fractional operator. ƒ : [0, 1] × R → R is continuous function. The second case, when 5 is a multi-valued mapping 0+ u (t) ∈ 5 (t, u (t)) , 0 < t < 1, (2) u (0) = u (1) = 0, where 1 < α < 2, 5 : [0, 1] × R → У (R) is a multivalue mapping and У (R) is the family of all subsets of R. cD is the standard Caputo fractional operator. The technique used in this work for to proving our results depends on the upper and lower solution, the Schauder fixed point theorem and the Banach and Covitz-Nadler contraction principle. ------------------------------------------------------------------------------ بشكل عام فإن وجود حلول للمعادلات التفاضلية العادية أو التضمينية الكسرية وغيرها من المسائل الرياضية تعتمد على نظرية النقطة الثابتة وغيرها من الطرق الأخرى. في هذا البحث، وباستخدام نظرية النقاط الثابتة، قدمنا بعض النتائج للمسائل التالية المتعلقة بالشروط الحدية: الحالة الأولى، عندما يكون 𝑓 تطبيقا حقيقيا 𝑐𝐷𝛼 𝑢 (𝑡) = 𝑓 (𝑡, 𝑢 (𝑡)), 𝑡 ∈ [0, 1] (1) 𝑢(0) = 𝑢(1) = 0 المؤثر الكسري لـ كابوتو و 𝑓 ×[0,1]: ℝ ← ℝ دالة مستمرة 𝑐𝐷𝛼 1 < 𝛼 < 2, حيث الحالة الثانية، عندما يكون 𝐹 تطبيقا متعدد القيم 𝑐𝐷𝛼 𝑢 (𝑡) ∈ (𝑡, 𝑢 (𝑡)), 𝑡 ∈ [0, 1] (2) متعدد القيم تطبيقا 𝑢(0) = 𝑢(1) = 0 المؤثر الكسري لـ كابوتو و 𝐹 ×[0,1]: ℝ ← P(ℝ) 𝑐𝐷𝛼 1 < 𝛼 < 2, حيث التقنية المستخدمة في هذا العمل لإثبات نتائجنا تعتمد على الحل العلوي والسفلي، ونظرية النقطة الثابتة لـ شودر، ومبدأ الانكماش لـ باناخ وكوفيتز نادلر. ------------------------------------------------------------------------------ En général, l'existence de solutions pour les équations différentielles fractionnaires ou l'inclusion et d'autres problèmes mathématiques sont aidés par l'étude de la théorie des points fixes et d'autres méthodes, etc. Dans ce mémoire, par la théorie des points fixes, nous donnons quelques résultats pour les problèmes suivants avec les conditions aux limites. Le premier cas, lorsque f est une application réelle 0+ u (t) = ƒ (t, u (t)) , t ∈ [0, 1], (1) u(0) = u(1) = 0 où 1 < α < 2, cD est l'opérateur fractionnaire standard de Caputo et ƒ : [0, 1] × R → R est continue. Le deuxième cas, lorsque 5 est une application, a des multiples valeurs. 0+ u (t) ∈ 5 (t, u (t)) , 0 < t < 1, (2) u (0) = u (1) = 0, avec 1 < α < 2, 5 : [0, 1] × R → У (R) est une application a multiples valeurs et У (R) est la famille de tous les sous-ensembles de R, cD est l'opérateur fractionnaire standard de Caputo. La technique utilisée dans ce travail pour prouver nos résultats dépend de la solution supérieure et inférieure, du théorème du point fixe Schauder et du principe de contraction de Banach et de Covitz-Nadler.
Keywords: Fractional derivative and integral; Upper and lower solutions; Fixed point theo- rems.: المشتق والتكامل الكسري. الحلول العلوية والسفلية. نظرية النقطة الثابتة.; Dérivée fractionnaire et intégrale; Solutions supérieures et inférieures; Théorème du point fixe.